1997
DOI: 10.1111/j.1471-0528.1997.tb12060.x
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren's syndrome in women presenting with chronic dyspareunia

Abstract: Objective To identify cases of Sjogren's syndrome among women with chronic dyspareunia who did not Design Prospective recruitment over 12 months.Setting Tertiary referral service for the assessment of vulva1 disease.Participants Women with chronic dyspareunia who had musculoskeletal symptoms, Raynaud's phenomenon or symptoms of ocular or oral dryness. MethodsThe women underwent a Schirmer tear test and a comprehensive auto-antibody screen including latex fixation test for rheumatoid factor, antinuclear, anti-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…In a case-control study of 36 women with 43 controls, 61% of the patients with Sjögren's syndrome described dyspareunia and 55% vaginal dryness, compared with 39% and 33% of controls respectively (Marchesoni et al 1995). In a study of patients presenting with dyspareunia who also complained of musculoskeletal symptoms, four of the 11 were found to have primary Sjögren's syndrome with positive antibodies and salivary gland histology (Mulherin et al 1997). It was noted that the vaginal symptoms seemed to predate the ocular and oral symptoms by many months.…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…In a case-control study of 36 women with 43 controls, 61% of the patients with Sjögren's syndrome described dyspareunia and 55% vaginal dryness, compared with 39% and 33% of controls respectively (Marchesoni et al 1995). In a study of patients presenting with dyspareunia who also complained of musculoskeletal symptoms, four of the 11 were found to have primary Sjögren's syndrome with positive antibodies and salivary gland histology (Mulherin et al 1997). It was noted that the vaginal symptoms seemed to predate the ocular and oral symptoms by many months.…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…Few studies have addressed gynaecological problems and fertility in pSS (2,3) as compared to other connective tissue diseases such as systemic lupus erythematosus (SLE) (4). Vaginal dryness and dyspareuni have been shown to be common and early manifestations of pSS (5). In the present case-control study, we have studied gynaecological aspects and fertility in women with pSS.…”
mentioning
confidence: 98%
“…Dyspareunia, pain with sexual intercourse, occurs more commonly in postmenopausal women due to estrogen deficiency that leads to vaginal atrophy. In SS, there is a disproportionately higher rate of dyspareunia reported among premenopausal women [26]. Skopouli et al reported that 40% of premenopausal SS patients reported dyspareunia compared to 3% among a healthy control population [24].…”
Section: Sjögren's Syndromementioning
confidence: 98%
“…The prevalence of dyspareunia among women with SS ranges from 40-69% [24][25][26][27]. Dyspareunia, pain with sexual intercourse, occurs more commonly in postmenopausal women due to estrogen deficiency that leads to vaginal atrophy.…”
Section: Sjögren's Syndromementioning
confidence: 99%